State of dendroflora of some parks in the city of Minsk - Strigelskaya, Nadezhda; Buchenkov, Igor; Chernetskaya, Alla (Journal of the Belarusian State University. Ecology, 2025)
The ecological potential of urban landscapes is determined mainly by the species composition, vegetation structure, stand age, the degree of failure and vital state of dominant species of woody plants, their resistance to environmental conditions. In this regard, at the first stage of the research the authors of the article defined the purpose of the study, which included the study of species composition, the degree of accident rate and vital state of condominant species of deciduous woody plants growing on the territories of landscape and recreational areas (urban parks) of Minsk with different degrees of anthropogenic pressure, other indicators will be studied in the future. Accident rate studies were carried out according to the methodology of flora monitoring as part of the National Environmental Monitoring System of the Republic of Belarus; the scale of V.S. Nikolaevsky (2002) was used to determine the vital state of woody plants. The results of the research include the determination of condominant species of woody plants (14 species) in large landscape and recreational zones of Minsk city belonging to different degrees of environmental conditions: Victory Park, Maksim Gorky Central Children’s Park, Loshitsky Manor Park Complex and Chelyuskintsev Park of Culture and Recreation. In the course of the study, 62 species of woody and shrubby plants belonging to 7 families were identified in the studied parks; the largest number of species is characteristic of the families Rosaceae, Willow, Pine and Maple. The article presents: the results of the study of the degree of accident rate of condominant species of deciduous woody plants (the most accidental are Malus domestica and Quercus robur); determination of the vital state of deciduous woody plants in the parks of Minsk (low scores are observed in Malus domestica and Quercus robur. At all investigated locations Tilia cordata and Acer platanoides have significant damage to the leaf laminae. Under urban conditions, high indicators of vital state are observed in Populus nigra on the territory of the Loshitsky estate-park complex and Betula pubescens on the territory of the Chelyuskintsev Park of Culture and Recreation, which corresponds to a relatively favorable zone of environmental conditions.
Keywords: dendroflora; condominant species; degree of accident; life state; landscape-recreational zones; Victory Park; Maxim Gorky Central Children’s Park; Loshitsky Manor Park Complex; Chelyuskintsev Park of Culture and Recreation